2009
DOI: 10.1590/s0034-70942009000400004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy Of Intraoperative Methadone And Clonidine In Pain Control In The Immediate Postoperative Period After The Use Of Remifentanil

Abstract: Methadone was more effective than clonidine in the control of postoperative pain in videolaparoscopic surgeries under total intravenous anesthesia with remifentanil; and using clonidine was not better than not using it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 31 publications
0
12
0
2
Order By: Relevance
“…Previous studies have reported differences between hypotensive anaesthesia based either on opioid antagonists like fentanyl or remifentanil, or on central acting agents like clonidine (19)(20)(21) . have a more favourable pharmacological profile, which offers better, more controlled haemodynamic management, with an optimized hypotensive effect during anaesthesia that allows safe bleeding control (28)(29)(30)(31) . In our previous observational cohort pilot study, we recorded a trend towards a better haemodynamic profile and heart rate estimates, lower bleeding scores and reduced surgery duration with clonidine as compared to an opioid-based regimen (22) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported differences between hypotensive anaesthesia based either on opioid antagonists like fentanyl or remifentanil, or on central acting agents like clonidine (19)(20)(21) . have a more favourable pharmacological profile, which offers better, more controlled haemodynamic management, with an optimized hypotensive effect during anaesthesia that allows safe bleeding control (28)(29)(30)(31) . In our previous observational cohort pilot study, we recorded a trend towards a better haemodynamic profile and heart rate estimates, lower bleeding scores and reduced surgery duration with clonidine as compared to an opioid-based regimen (22) .…”
Section: Discussionmentioning
confidence: 99%
“…Recovery Times. Time to extubation was reported in five trials, 16,20,30,39,40 time to spontaneous eye opening in four, 25,30,36,39 and time to response to verbal command in nine ( 16,19,25,28,30,34,35,39,40 In dexmedetomidine trials, the median of all average times to extubation in control subjects was 7.0 min (range, 5.7-7.5). Dexmedetomidine significantly shortened that time (WMD Ϫ1.6 min).…”
Section: Postoperative Consumption Of Morphine Equivalentsmentioning
confidence: 99%
“…At this moment, it is indicated the use of long-lasting opioids. The methadone is an effective alternative to conventional opioids to control postoperative pain 38,44,[51][52][53][54][55] .…”
Section: Perioperative Periodmentioning
confidence: 99%